Acute Traumatic Cervical Facet Fractures - Shankar Gopinath (Indoscholar, 2018)
Acute cervical facet fractures are increasingly being detected due to the use of cervical spine CT imaging in the initial assessment of trauma patients. For displaced cervical facet fractures with dislocations and subluxations, early surgery can decompress the spinal cord and stabilize the spine. For patients with non-displaced cervical facet fractures, the challenge in managing these patients is the determination of spinal stability. Although many of the patients with non-displaced cervical facet fractures can be managed with a cervical collar, the imaging needs to be analyzed carefully since certain fracture patterns may be better managed with early surgical stabilization.